Electrospun polycaprolactone/silk fibroin nanofibrous bioactive scaffolds for tissue engineering applications. (2nd April 2019) - Nazeer, Muhammad Anwaar; Yilgor, Emel; Yilgor, Iskender
Abstract: Degumming of Bombyx mori silk cocoons by a novel and mild process using aqueous ammonia and fabrication of electrospun polycaprolactone/silk fibroin (PCL/SF) nanofibrous scaffolds is reported. Cocoons were degummed in 0.3% w/w solutions of boiling ammonia (28–30%) for 45 min. Degummed SF fibers were dissolved in phosphoric and formic acid (7/3 v/v) mixture, coagulated in methanol, filtered and dried. PCL solutions containing different amounts of SF were electrospun in formic acid, a green solvent. Scaffolds were characterized to confirm the successful incorporation of SF and to demonstrate formation of nanofibrous webs with good biomechanical properties. Cell viability assay was performed by seeding Human BJ fibroblast cells on scaffolds. In vitro analysis showed that the scaffolds produced were non-toxic and incorporation of SF resulted in enhanced cell proliferation. Nanofibrous PCL/SF scaffolds with good biomechanical properties developed through dialysis free processing of silk fibroin can be promising substrates for tissue engineering applications. Graphical abstract: Image 1 Highlights: Ammonia is a mild and efficient degumming reagent for sericin removal. Ammonia degummed fibers display smooth surfaces without any hydrolytic damage. Formic acid is a good, green solvent for electrospinning of PCL/SF composite fibrous scaffolds. Incorporation of SF into electrospun PCL scaffolds improves cell adhesion and proliferation significantly. Electrospun PCL/SF scaffolds are promising substrates for tissue engineering applications.